"She is more about my illness than me": a qualitative study exploring social support in individuals with experiences of psychosis. Issue 2 (2nd April 2020) - McGuire, Nicola; Melville, Craig; Karadzhov, Dimitar; Gumley, Andrew
ABSTRACT: Experiences of psychosis may increase isolation and stigma, increasing negative perceptions of oneself. Social networks can be a source of support and strain in dealing with these difficulties. This research explored how individuals with experiences of psychosis make sense of their social relationships. Interpretative Phenomenological Analysis guided the design and conduct of semi-structured interviews with seven Scottish mental health service-users with lived experience of psychosis, exploring positive and negative aspects of relationships and how they influenced personal recovery. Interviews were audio-recorded, transcribed and coded for subordinate and superordinate themes. The superordinate theme "She is more about my illness than me" highlighted normalisation of participants' illness identity through family and support staff dominating social networks; their primary orientation being towards illness management. Subordinate themes; "without the service I wouldn't know what to do", "They wouldn't talk, they will sort of control me in a way" and "She doesn't see me as normal either with me getting help" evidenced benefits and tensions associated with these relationships. The composition and nature of social networks can prevent individuals with experiences of psychosis from exploring identities unrelated to illness. Further research must identify ways to empower individuals and promote connectedness independently from illness management.